One Hundred Years of Bloodshed: The Extermination of Christians by Muslims in the Ottoman Empire, 1822–1922 - Tseligka, Eleni 1973- (2025)
This paper argues that the Armenian genocide, the genocide of the Greeks of Pontus and the Greek Catastrophe, and the Nestorian and Assyrian genocide, all of which took place during the late Ottoman Empire, were not isolated historic incidents, but rather different phases of a broader agenda of Christian extermination in Asia Minor. The early 19th-century Ottoman Christian scepticism over the established status quo of the millet system, which had served as a platform of religious conflict resolution and intercultural dialogue but dictated subordination to Islam, was perceived as defiance by Ottoman Muslims, who interpreted the Christian strife for social equality as the loss of their privilege, thus creating bottom-up pressure for violence, resulting in the genocide and ethnic cleansing of the majority of Ottoman Christians between 1822 and 1922.
Keywords: millet system; Ottoman Empire; Pontic Greek genocide; Armenian Genocide; Greek Catastrophe; Christian genocide